2019
DOI: 10.1016/j.canlet.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of JunD in cell proliferation is mediated via MYC signaling in prostate cancer cells

Abstract: JunD, a member of the AP-1 family, is essential for cell proliferation in prostate cancer (PCa) cells. We recently demonstrated that JunD knock-down (KD) in PCa cells results in cell cycle arrest in G 1 -phase concomitant with a decrease in cyclin D1, Ki67, and c-MYC, but an increase in p21 levels. Furthermore, the over-expression of JunD significantly increased proliferation suggesting JunD regulation of genes required for cell cycle progression. Here, employing gene expression profiling, quantitative proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 91 publications
4
34
0
Order By: Relevance
“…It has been confirmed by studies that NRIP3 and RASL11B play a role in suppressing cancer proliferation in breast cancer and renal cell carcinoma [31,32]. Meanwhile ALPP, JUND, ZBTB7A in gastric cancer, prostate cancer, breast cancer [33][34][35] and other cancers promote the progress of cancer. Thence, we can boldly speculate that PRKACB plays a synergistic role with these tumor suppressors in inhibiting tumor growth.…”
Section: Discussionmentioning
confidence: 90%
“…It has been confirmed by studies that NRIP3 and RASL11B play a role in suppressing cancer proliferation in breast cancer and renal cell carcinoma [31,32]. Meanwhile ALPP, JUND, ZBTB7A in gastric cancer, prostate cancer, breast cancer [33][34][35] and other cancers promote the progress of cancer. Thence, we can boldly speculate that PRKACB plays a synergistic role with these tumor suppressors in inhibiting tumor growth.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Elliott B reported that JUND was a crucial modulator in prostate cell cycle progression and thus promoting cancer development. 38 Ishikawa et al found that Butein ameliorated adult leukemia via inhibiting JUND expression. 39 Cheng et al also revealed that JUND was involved in cancer stemness and drug resistance in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc is one of the most important drivers and effectors in promoting the carcinogenesis of pancreatic cancer via the modulation of cell metabolism, cellular growth, metastasis, and apoptosis [4648] and understanding the regulatory mechanism of c-Myc highlights novel therapeutic strategies for pancreatic cancer. c-Myc is reported to be controlled by many transcriptional factors, including JunD [49], BRD4 [50], and APC [51]. The abnormal activation of oncogenic pathways, such as the PI3K/AKT pathway [52] or MAPK pathway [53], increases c-Myc levels in cancer cells.…”
Section: Discussionmentioning
confidence: 99%